Peranan Koperasi Terhadap Kesejahteraan Santri dan Pembangunan Infrastruktur di Pondok Pesantren Miftahul Ulum - Rifki Iqbalul Umam; Doni Teguh Wibowo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
In the economic domain, cooperatives represent a form of collaboration that emerges from shared needs among individuals within a community. One of the Pesantren-Owned Enterprises operating at Pondok Pesantren Miftahul Ulum Putra is a cooperative, which serves to support and strengthen the pesantren’s economic foundation. This study aims to examine the role of pesantren cooperatives (kopontren) in improving the economic welfare of santri and their contribution to the development of pesantren infrastructure. The research was conducted at Pondok Pesantren Miftahul Ulum Putra using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the kopontren plays a strategic role in providing basic necessities for santri at affordable prices, while also functioning as a practical learning platform for economic education that fosters entrepreneurial spirit and self-reliance. Although its contribution to infrastructure remains limited, the kopontren has begun to demonstrate social responsibility through the provision of supporting facilities such as dormitory furniture and environmental maintenance. The synergy between cooperative management and pesantren leadership is a key factor in sustaining the cooperative as an integral part of the pesantren’s educational system.